Loop-Mediated Isothermal Amplification Methods for Diagnosis of Bacterial Meningitis - Seki, Mitsuko; Kilgore, Paul E.; Kim, Eun Jin; Ohnishi, Makoto; Hayakawa, Satoshi; Kim, Dong Wook (Frontiers in Pediatrics, 2018)
The rapid, accurate, and efficient identification of an infectious disease is critical to ensure timely clinical treatment and prevention in public health settings. In 2015, meningitis caused by Streptococcus pneumoniae, Haemophilus influenzae, and Neisseria meningitidis was responsible for 379,200 (range: 322,700–444,700) deaths. Clinical features alone cannot determine whether bacterial meningitis is present; an analysis of cerebrospinal fluid (CSF) is essential. Loop-mediated isothermal amplification (LAMP) is a nucleic acid amplification method offering an alternative to polymerase chain reaction (PCR). LAMP-based assays for detection of three leading bacteria in CSF for diagnosis of meningitis have been established. The typing assays using LAMP for detection of meningococcal serogroups A, B, C, W, X, and Y as well as H. influenzae serotypes a, b, c, d, e, and f were launched. In comparative analysis of the meningitis pathogen assays, LAMP assays did not yield false negative results, and the detection rate of LAMP assays was superior compared with PCR or conventional culture methods. LAMP assays provide accurate and rapid test results to detect major bacterial meningitis pathogens. Accumulating evidence suggests that LAMP assays have the potential to provide urgently needed diagnostics for bacterial meningitis in resource-limited settings of both developed and developing countries.